Gênero, branquitude e racismo : mulheres que criminalizam outras mulheres e sua relação com a lei de drogas no judiciário do Rio Grande do Sul - Moreira, Alena Ocom (2022)
This dissertation addresses the connection between gender, whiteness, and racism in the lives and decisions of women in positions of power in the judiciary of Rio Grande do Sul and its relation to the Drug Law (Law number 11.343/2006). The study problematizes from the power dynamics and places they occupy, how they see themselves within a structure permeated by gender, racism, and whiteness, and the possibility of reflections regarding the impacts of this law. It highlights the perceptions of their experiences working in the judiciary, as well as the identification of the unproductiveness of a hierarchy of oppressions to analyze reality. In this sense, we operate with race, gender, and social class, as categories of analysis applied in connection, to identify a new form of perception of the systems of power, especially the Brazilian judicial and criminal system. As well as the way that these three structures, forged by whiteness, are being reconfigured throughout the historical process within the criminal justice system, perpetuating the maintenance of inequalities and crystallizing the social place occupied by women. The research is positioned in the field of Criminal Sciences, with a qualitative perspective, using as methodological approach the comprehensive interview. Intersectionality is used as an analytical tool and conceptual basis, which highlights the impossibility of conceiving systems of oppression without understanding how gender, race and social class are connected in favor of systems of domination. The intersectional approach makes it possible to face discrimination effectively and simultaneously, guiding inclusive public policy actions based on women's real needs. It is important to emphasize that the comprehensive interview goes beyond the limits of being used only as a methodological support to face historically structured themes. We resorted to orality as an epistemological choice that provides support to a socially committed research within a social context impacted by a global pandemic of unprecedented proportions, which implied the analysis of differentiated physical and social elements, revealing particularities of the vision of women who are in the highest ranks of the judicial hierarchy, highlighting the uniqueness of each of the narratives, enabling the construction of paths for change from within.